1992
DOI: 10.1002/lsm.1900120409
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coaxial CO2/Nd:YAG irradiation on periodontal wound healing

Abstract: This study evaluated a coaxial CO2/Nd:YAG laser used during periodontal surgery in mongrel dogs for the purpose of ablating the osseous portions of root surfaces to increase reattachment of soft tissue. Periodontal defects were produced with ligatures of orthodontic wire and elastics. The left mandibular osseous root surfaces were irradiated with a defocused, CW laser beam [power density (PD) = 42.46 W/cm2, energy density (ED) = 424.63 J/cm2]. The left maxillary osseous root surfaces were treated with a beam a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Despite apparent benefits of lasers regarding patient compliance and clinical observation, there are no enough data to support that laser is associated with reduced scarring, which itself appears to be different according to the wavelength and extremely related to the energy density, and there are no enough data to support quicker healing associated with laser therapy [13]. Limited experimental animal studies [68,69] involving CO 2 ,Nd:YAG, diode lasers, or Er:YAG have evaluated the histological and immunohistochemical patterns of periodontal tissue healing following surgical and nonsurgical periodontal therapy. Sculean et al [70] and Yukna et al [71] reported healing response of intrabony defects after open flap surgery or treatment using a laser-assisted new attachment procedure in humans using Er:YAG and Nd:YAG lasers, respectively.…”
Section: Healing Following Laser Therapymentioning
confidence: 99%
“…Despite apparent benefits of lasers regarding patient compliance and clinical observation, there are no enough data to support that laser is associated with reduced scarring, which itself appears to be different according to the wavelength and extremely related to the energy density, and there are no enough data to support quicker healing associated with laser therapy [13]. Limited experimental animal studies [68,69] involving CO 2 ,Nd:YAG, diode lasers, or Er:YAG have evaluated the histological and immunohistochemical patterns of periodontal tissue healing following surgical and nonsurgical periodontal therapy. Sculean et al [70] and Yukna et al [71] reported healing response of intrabony defects after open flap surgery or treatment using a laser-assisted new attachment procedure in humans using Er:YAG and Nd:YAG lasers, respectively.…”
Section: Healing Following Laser Therapymentioning
confidence: 99%
“…One study attempted to evaluate periodontal wound healing in dogs after irradiation using a coaxial CO 2 ⁄ Nd:YAG laser (5). Chronic periodontal defects were experimentally induced at the furcation and interproximal areas of either maxillary or mandibular premolars and molars.…”
Section: Experimental Studies On the Treatment Of Periodontal Diseasementioning
confidence: 99%
“…The most commonly used lasers in this group are the gallium‐aluminum‐arsenide (GaAlAs) laser (810 nm) and the indium‐gallium‐arsenide‐phosphide (InGaAsP) laser (980 nm). Diode lasers operate in continuous wave and/or pulsed modes and are very effective for use in soft‐tissue applications with excellent effects of incision, hemostasis and coagulation (5). These specific wavelengths are well absorbed in hemoglobin and pigmented tissue (Fig.…”
Section: In Vitro Studies On Tissue Interactions Of Different Laser Wmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, to achieve osseous ablation by laser, higher power settings and longer exposure times are generally required, increasing the risk of collateral tissue damage. Over the last decade, numerous investigators have studied the effect of the COz laser (and to a lesser extent the Nd:YAG) on bone, but generally at energy densities greater than those suggested for soft tissue surgery (4,11,13,29,42,61,84,93). Three distinct histological zones may be delineated in laser-treated bone: a superficial char zone, an intermediate zone of nonvital heat-damaged bone featuring empty lacunae and a deep zone of normal bone (70,71).…”
Section: Laser-bone Interactionsmentioning
confidence: 99%